Hsa_circ_0060927 Is a Novel Tumor Biomarker by Sponging miR-195-5p in the Malignant Transformation of OLK to OSCC - Xu, Siming; Song, Yuhan; Shao, Yanxiong; Zhou, Haiwen (Frontiers in Oncology, 2022)
Objective: To investigate the clinical significance of differentially expressed circRNAs and candidate circRNAs in the transformation of oral leukoplakia (OLK) to oral squamous cell carcinoma (OSCC). Methods: High throughput circRNA sequencing was performed in 6 cases of normal oral mucosal (NOM) tissues, 6 cases of OLK tissues and 6 cases of OSCC tissues. 10 circRNAs with significant differential expression were verified by qRT-PCR. Enzyme tolerance assay and Sanger sequencing was performed on the screened target circRNA hsa_circ_0060927, and a qRT-PCR assay of hsa_circ_0060927 was performed in the three tissues (24 cases in each group), and ROC analysis was proceeded. The ceRNA network was predicted using TargetScan and miRanda. MiR-195-5p and TRIM14 were selected as the downstream research objects of hsa_circ_0060927. The sponge mechanism of hsa_circ_0060927 was detected by AGO2 RIP. The interaction between hsa_circ_0060927 and miR-195-5p was verified by RNA pull down assay and dual luciferase reporter gene assay. The expression of hsa_circ_0060927, miR-195-5p and TRIM14 were verified by normal oral epithelial primary cells and cell lines of LEUK1, SCC9 and SCC25. The hsa_circ_0060927 overexpressed plasmid and miR-195-5p mimics were constructed to transfection LEUK1 to detect the changes in cell proliferation, apoptosis and migration. Results: The results of qRT-PCR validation were consistent with the sequencing results. Hsa_circ_0060927 is a true circRNA with trans-splicing sites. The expression of hsa_circ_0060927 increased in NOM, OLK and OSCC. Overexpression of hsa_circ_0060927 enhanced the ability of cell proliferation and migration, and decreased cell apoptosis capacity. The prediction of ceRNA network suggested that hsa_circ_0060927 could regulate the target gene TRIM14 through sponging miR-195-5p. AGO2 RIP indicated that hsa_circ_0060927 had sponge mechanism. RNA pull down and dual luciferase reporter gene assay suggested that hsa_circ_0060927 interacted with miR-195-5p. Hsa_circ_0060927 was positively correlated with the expression of TRIM14, and could relieve the inhibition of miR-195-5p on TRIM14 to regulate cell proliferation, apoptosis and migration of LEUK1 cells. Conclusion: Hsa_circ_0060927 acts as a potential key ceRNA to sponge downstream miR-195-5p and promote OLK carcinogenesis by upregulating TRIM14. Hsa_circ_0060927 is expected to be a molecular marker for the prevention and treatment of OLK carcinogenesis through hsa_circ_0060927 /miR-195-5p/TRIM14 axis.